DESAIN GAME ONLINE MATEMATIKA MENGGUNAKAN HTML DAN FLASH DALAM PERKULIAHAN MULTIMEDIA PENDIDIKAN MATEMATIKA BERBANTUAN E-LEARNING - Eyus Sudihartinih; Dewi Rachmatin (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
This study aims to obtain a description of online mathematical game design using HTML and Flash in e-learning-assisted mathematics education multimedia lectures. This research is a pre-experimental type of one-shot case study. The research participants were a class of students consisting of 34 people (5 men and 29 women), 5th- semester students in multimedia mathematics education courses in the mathematics education department at one of the universities in Indonesia. The research instrument was a questionnaire through Google forms and interviews. In this study, triangulation was carried out using documentation, interviews, and theory. Based on the results of the study note that HTML and Flash can be used in the design of mathematical games even though students have not previously learned both but the results are good. The author suggests that students be able to try the math game at school during research or teaching practice. In addition, the authors hope the game can be published on the internet so that it can be used by many students.